History & truth in Hegel's Phenomenology - Westphal, Merold (Indiana University Press, 2010)
1. The task of the phenomenology: the introduction. Critical philosophy as the fear of error and the fear of truth -- Phenomenology as the way of doubt and dispair -- ... as criticism without presuppositions. 2. The preface. The present standpoint of spirit -- The life-world of critical philosophy -- The medical function of philosophy: midwifery; socioanalysis. 3. The knowledge of nature: sens perception. "The truth is the whole" as hermeneutical guide -- The mediated character of sense perception -- Language, sense certainty, and Feuerbach's critique -- Language and the double mediation of theoretical consciousness -- Sense certainty and the phenomenology as a whole. 4. Natural science. Preliminary sketch of Hegel's phenomenological philosophy of science -- The supersensible character of scientific thought -- The tautological character of scientific explanation -- The transcendental source of science's supersensible tautologies.